2020
DOI: 10.1007/s40265-020-01377-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Thrombotic Complications in COVID-19: An Update

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is now a global pandemic. This virus primarily affects the respiratory tract and causes lung injury characterized by acute respiratory distress syndrome. Although the pathophysiology of COVID-19 is not yet clear, the most widely accepted mechanism is systemic inflammation. A clinically significant effect of the inflammation is coagulopathy. As a result of this effect, patients are found to have a high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 60 publications
0
69
0
16
Order By: Relevance
“…The treatment with a full dose of anticoagulation may be beneficial for patients with sepsis-induced coagulopathy (SIC). 121 In a retrospective study by Tang et al, 122 the use of heparin was shown to reduce mortality in patients who met the SIC criteria or had a markedly increased D -dimer levels. In patients with a thromboembolic event or an increased suspicion for thromboembolic disease, therapeutic anticoagulation is recommended.…”
Section: Management Of Hematological Abnormalities In Covid-19mentioning
confidence: 99%
“…The treatment with a full dose of anticoagulation may be beneficial for patients with sepsis-induced coagulopathy (SIC). 121 In a retrospective study by Tang et al, 122 the use of heparin was shown to reduce mortality in patients who met the SIC criteria or had a markedly increased D -dimer levels. In patients with a thromboembolic event or an increased suspicion for thromboembolic disease, therapeutic anticoagulation is recommended.…”
Section: Management Of Hematological Abnormalities In Covid-19mentioning
confidence: 99%
“…COVID-19 is a prothrombotic state leading to both microvascular and macrovascular thromboembolic events in pulmonary and extrapulmonary organs (136). Venous thromboembolism, particularly pulmonary embolism, is the most common coagulopathic manifestation in COVID patients (137). Several proposed mechanisms for thrombosis in COVID-19 patients include angiotensin-converting enzyme-2 receptor-mediated endothelial damage leading to cytokine storm, intussusceptive angiogenesis, and macrophage activation syndrome leading to activation of the coagulation cascade (136)(137)(138)(139).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Venous thromboembolism, particularly pulmonary embolism, is the most common coagulopathic manifestation in COVID patients (137). Several proposed mechanisms for thrombosis in COVID-19 patients include angiotensin-converting enzyme-2 receptor-mediated endothelial damage leading to cytokine storm, intussusceptive angiogenesis, and macrophage activation syndrome leading to activation of the coagulation cascade (136)(137)(138)(139). The incidence of thrombotic events in COVID patients is 7.7-49% in various retrospective and prospective studies (140)(141)(142)(143)(144).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Disseminated intravascular coagulation and thrombotic microvascular occlusion are complications of severe systemic inflammation and a sequela to most infections discussed in this article ( Table 1 ). Notably, COVID-19 has been strongly associated with thrombosis ( 85 ), more so than other coronaviruses and H1N1 ( 39 ). This is not entirely surprising, as severely ill SARS-CoV-2-infected patients have intra-endothelial viral inclusion bodies, endothelial apoptosis, and inflammation (endotheliitis) ( 2 4 ).…”
Section: Endothelial Function In Homeostasis and Inflammationmentioning
confidence: 99%